2018
DOI: 10.1007/s40194-018-0634-2
|View full text |Cite
|
Sign up to set email alerts
|

Static strength and design of aluminium-to-steel thin welded joints

Abstract: Welding together dissimilar materials, and, in particular, aluminium alloys to steel, has always been a challenge because of the significant difference in their mechanical, thermo-physical and metallurgical properties which causes the formations of hard and brittle intermetallic phases in the welding region. Recently, EWM® has developed a welding process known as ColdArc®, where the heat input and arc stability are precisely controlled. The present study was designed to investigate the static strength of alumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Some of them were improved when the evaluation becomes more complex and a multiaxial stress state occurs [43,[56][57][58][59][60][61]. Recently, the abovementioned approaches were further assessed with several contributions, i.e., the cyclic structural stress was further developed by Dong [62,63] and extended in terms of structural strain of the LCF assessment [64,65], the elastic notch effect was reviewed in [66], the notch stress intensity approaches were deeply discussed in [66][67][68] and the peak-stress method was validated for many kinds of joints and was related to the SED and NSIF approaches [67,69].…”
Section: Figure 12mentioning
confidence: 99%
See 2 more Smart Citations
“…Some of them were improved when the evaluation becomes more complex and a multiaxial stress state occurs [43,[56][57][58][59][60][61]. Recently, the abovementioned approaches were further assessed with several contributions, i.e., the cyclic structural stress was further developed by Dong [62,63] and extended in terms of structural strain of the LCF assessment [64,65], the elastic notch effect was reviewed in [66], the notch stress intensity approaches were deeply discussed in [66][67][68] and the peak-stress method was validated for many kinds of joints and was related to the SED and NSIF approaches [67,69].…”
Section: Figure 12mentioning
confidence: 99%
“…Some of them were improved when the evaluation becomes more complex and a multiaxial stress state occurs [43,[56][57][58][59][60][61].…”
Section: Figure 12mentioning
confidence: 99%
See 1 more Smart Citation
“…The range of HAZ is distributed 20 mm from the fusion line with a plate thickness of 5 mm. I. Al Zamzami et al (2018) investigated the static load capacity of steel-aluminium welded joints [7]. In their work, they concluded that the welding of different materials, especially aluminium alloys with steel, has always been a challenge due to the significant difference in their mechanical, thermo-physical and metallurgical properties that cause the formation of hard and brittle intermetallic phases in the welding area.…”
Section: Introductionmentioning
confidence: 99%
“…In the work of Liu and Ren, 11) they found that the adhesiveinduced gas would reduce the energy required to penetrate the upper sheet so that higher laser power density could interact with the lower sheet, leading to deeper penetration. Zhou et al 12,13) investigated the microstructure and mechanical properties of laser spot weld-bonding joints of DP590 dual-phase steel to aluminum alloy, the results pointed out that welding defects could be avoided, welding penetration depth and width increased compared with those of laser welding. Farabi et al 14) found that the soften zone formed in the laser welding process had a greater effect on the laser welding joints of DP980 compared with DP600.…”
Section: Introductionmentioning
confidence: 99%